Comparison of DNA methylation profiles associated with spontaneous preterm birth in placenta and cord blood - Xi-Meng Wang; Fu-Ying Tian; Li-Jun Fan; Chuan-Bo Xie; Zhong-Zheng Niu; Wei-Qing Chen (BMC, 2019)
Abstract Background The etiology and mechanism of spontaneous preterm birth (sPTB) are still unclear. Accumulating evidence has documented that various environmental exposure scenarios may cause maternal and fetal epigenetic changes, which initiates the focus on whether epigenetics can contribute to the occurrence of sPTB. Therefore, we conducted the current study to examine and compare the DNA methylation changes associated with sPTB in placenta and cord blood. Methods This hospital-based case-control study was carried out at three Women and Children's hospitals in South China, where 32 spontaneous preterm births and 16 term births were recruited. Genome-wide DNA methylation profiles of the placenta and cord blood from these subjects were measured using the Illumina HumanMethylation EPIC BeadChip, and sPTB-associated differential methylated CpG sites were identified using limma regression model, after controlling for major maternal and infant confounders. Further Gene Ontology analysis was performed with PANTHER in order to assess different functional enrichment of the sPTB-associated genes in placenta and cord blood. Results After controlling for potential confounding factors, one differentially methylated position (DMP) in placenta and 31 DMPs in cord blood were found significantly associated with sPTB (Bonferroni corrected p < 0.05). The sPTB-associated CpG sites in placenta were mapped to genes that showed higher enrichment on biological processes including biological regulation, multicellular organismal process, and especially response to stimulus, while those in cord blood were mapped to genes that had higher enrichment on biological processes concerning cellular process, localization, and particularly metabolic process. Conclusion Findings of this study indicated that DNA methylation alteration in both placenta and cord blood are associated with sPTB, yet the DNA methylation modification patterns may appear differently in placenta and cord blood.